Interactions between surfactants and {1,4-phenylene-[9,9-bis(4-phenoxy-butylsulfonate)]fluorene-2,7-diyl} - Burrows, H. D. (2005)
The interaction between the water-soluble anionic conjugated copolymer poly{1,4-phenylene-[9,9-bis(4-phenoxy-butylsulfonate)]fluorene-2,7-diyl} (PBS-PFP) and various surfactants has been studied in aqueous solution by UV-vis absorption spectra, fluorescence and electrical conductivity. It is suggested from the linear dependence of absorbance, fluorescence and electrical conductivity on concentration that in the absence of surfactant, moderately stable dispersions are formed. These are affected in different ways on adding cationic, anionic or neutral surfactants. With the cationic cetyltrimethylammonium bromide, quenching of fluorescence intensity and lifetime, and formation of a new emission occurs at concentrations well below the critical micelle concentration (cmc). Electrical conductivity measurements indicate a discontinuity at surfactant/polymer ratio corresponding to electroneutrality, due to complexation. With the anionic sodium dodecyl sulfate, fluorescence quenching is also observed, but is attributed to formation of some mixed polymer/surfactant aggregate. The most striking changes are observed with the non-ionic pentaethyleneglycol monododecyl ether (C12E5), where a blue shift in fluorescence emission, dramatic increases in lifetime and quantum yield, and changes in electrical around the cmc are interpreted in terms of incorporation of single polymer chains in elongated cylindrical micelles. This is supported by 1H NMR spectroscopic measurements.